PENGARUH MANFAAT DAN KEMUDAHAN PENGGUNA TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN MOBILE BANKING BANK MANDIRI - Dina Marisa Lumbantoruan; Anne Rumondang Malau; Hanna Melani Damanik; Leonardo Davidsi Sipayung (LP2M Universitas Bina Bangsa, 2023)
This study aims to determine the effect of benefits and ease of use on customer decisions to use Bank Mandiri Mobile Banking in Medan City. This research was conducted from August to September 2022 at Bank Mandiri Medan. This type of research is quantitative research using descriptive analysis. The population in this study is all customers who use Mobile Banking with a total of 4,103 customers.and the sample in this study is 100 customers from the population selected with Purposive Sampling Technique. Data collection was carried out using questionnaires using Likert scale measurements. The test of the research instrument used is a validity test and a reliability test. The data analysis technique used in this study is multiple linear regression analysis, namely Y = 0.921 + 0.351X1 + 0.465X2 + e. The results of this study show that: benefits have a positive and significant effect on customer decisions using Bank Mandiri Mobile Banking with a significance value of 2,206 > 0.30. Ease of use has a positive and significant effect on customers' decisions to use Bank Mandiri Mobile Banking with a significance value of 3,785 > 0.00